Pengaruh NPL dan BOPO Terhadap Return On Assets pada bank yang terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Vidory Mandala; Made Denny Oktariyana; Eugenia H. P. Tanan (Jurnal Inovasi Akuntansi (JIA), 2023)
This research was conducted on banking companies listed on the Indonesia Stock Exchange in 2018-2022. The purpose of this study is to determine the effect of NPL and BOPO on partial Return On Assets. This study used quantitative descriptive method, i.e. data obtained from secondary data. The sampling method obtained was as many as 11 banking companies. The data analysis technique used is multiple linear regression analysis technique. The results of this study show that NPL has a negative and significant effect on ROA while BOPO has a positive and insignificant effect on ROA. This is evident from the test results partially with significant on the ROA ratio.